1995
DOI: 10.1083/jcb.131.6.1649
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic localization of RNase MRP RNA in the nucleolus observed by fluorescent RNA cytochemistry in living cells.

Abstract: Abstract. The dynamic intra-nuclear localization of MRP RNA, the RNA component of the ribonucleoprotein enzyme RNase MRP, was examined in living cells by the method of fluorescent RNA cytochemistry (Wang, J., L.-G. Cao, Y.-L. Wang, and T. Pederson. 1991. Proc. Natl. Acad. Sci. USA. 88:7391-7395). MRP RNA very rapidly accumulated in nucleoli after nuclear microinjection of normal rat kidney (NRK) epithelial cells. Localization was specifically in the dense fibrillar component of the nucleolus, as revealed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 42 publications
4
92
0
3
Order By: Relevance
“…12,28 Mutations in RMRP seem to avoid nucleotides 23 -62 which have been reported to be a nucleolar localisation signal region. 27 We found a compound heterozygous mutation at nucleotide 57 in one patient, but due to the sequence content of this duplication it does not change the sequence of the nucleolar localisation signal. On the other hand, the mitochondrial localisation signal region has been reported to reside between nucleotides 118 -175 in the mouse 29 which corresponds to nucleotides 118 -167 in the human RMRP.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…12,28 Mutations in RMRP seem to avoid nucleotides 23 -62 which have been reported to be a nucleolar localisation signal region. 27 We found a compound heterozygous mutation at nucleotide 57 in one patient, but due to the sequence content of this duplication it does not change the sequence of the nucleolar localisation signal. On the other hand, the mitochondrial localisation signal region has been reported to reside between nucleotides 118 -175 in the mouse 29 which corresponds to nucleotides 118 -167 in the human RMRP.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, we have characterised herein three insertions and duplications in the 5' end of the transcript, which form a third group of mutations in RMRP. These mutations are gathered around the nucleolar localisation signal region 27 and the regions reported to be important for binding the different proteins of the RNase MRP complex. 13 Only heterozygosity of insertion and further duplication mutations in the promoter region or 'null' alleles of RMRP were detected, further suggesting that expression of the RNase MRP RNA is indeed essential for life.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior of topo I closely resembles that of RNA polymerase I itself (21,25). Thus, topo I does not make an exception to the general rule that molecules are targeted to the nucleolus due to their interaction with one of the three nucleolar building blocks that are structured around rDNA and/or its transcripts (35)(36)(37). Even during mitosis, where rDNA is not transcribed, topo I remains associated with the corresponding chromosomal structures that harbor rDNA and RNA polymerase I (5,38,39).…”
Section: Discussionmentioning
confidence: 78%
“…P3 domain comparisons from RNase P and RNase MRP RNAs+ A: Secondary structure of S. cerevisiae RNase P RNA based on phylogenetic and biochemical analysis (Tranguch et al+, 1994)+ The location of the P3 RNA domain is shown in bold+ The location and sequence of the inserted hybridization tag (Bertrand et al+, 1998) between positions 133 and 139 is shown in italics+ B: P3 RNA domains from RNase P and MRP are shown from five eukaryotes, with intraspecies nucleotide conservations in bold+ S. cerevisiae and S. pombe RNase P sequence is from Tranguch & Engelke (1993) and Krupp et al+ (1986); human, mouse, and X. laevis RNase P is from Pitulle et al+ (1998); S. pombe RNase MRP is from Paluh and Clayton (1995); S. cerevisiae, human, mouse, and X. laevis RNase MRP is from Schmitt et al+ (1993)+ Engelke, 1993;Paluh & Clayton, 1995;Pitulle et al+, 1998)+ The P3 domains from Saccharomyces cerevisiae RNases P and MRP have been shown to be functionally equivalent, because swapping domains between enzymes was permitted (Lindahl et al+, 2000)+ Minimization experiments using domain deletions from yeast RNase P RNA have shown the P3 domain to be essential for generating a functional enzyme (PaganRamos et al+, 1994)+ Recent studies have further identified the P3 domain, in both human RNase P and RNase MRP, as required for binding the To antigen, a 40-kDa protein immunoprecipitated by human autoimmune sera (Reddy et al+, 1983;Liu et al+, 1994;Eder et al+, 1997)+ Microinjection experiments using synthetic RNase MRP RNA result in nucleolar localization of the RNA, consistent with the role of RNase MRP in processing prerRNA (Jacobson et al+, 1995)+ Microinjected RNase P RNA alone localized to the nucleolus only transiently (Jacobson et al+, 1997)+ Transient nucleolar localization of RNase P RNA was dependent on the P3 domain, suggesting a potential role for P3 in nucleolar localization+ It is currently not clear whether RNase P is also a nucleolar enzyme, and to what extent this is consistent among species+ Yeast nuclear RNase P appears largely nucleolar (Bertrand et al+, 1998), and in situ studies of mammalian RNase P have indicated either transient nucleolar association (Jacobson et al+, 1997) or limited steady-state localization to a "perinuclear compartment" (PNC) located on the nucleolar periphery (Matera et al+, 1995;Lee et al+, 1996)+ It has not been clear from these data whether the role of the P3 domain in localization is to direct holoenzyme assembly, which in turn causes localization, or whether the RNA interacts directly with some...…”
Section: Introductionmentioning
confidence: 87%